Do sensorimotor cortex activity, an individual's capacity for neuroplasticity, and psychological features during an episode of acute low back pain predict outcome at 6 months: a protocol for an Australian, multisite prospective, longitudinal cohort study. Issue 5 (22nd May 2019) - Jenkins, Luke C; Chang, Wei-Ju; Buscemi, Valentina; Liston, Matthew; Toson, Barbara; Nicholas, Michael; Graven-Nielsen, Thomas; Ridding, Michael; Hodges, Paul W; McAuley, James H; Schabrun, Siobhan M
Abstract : Introduction: Low back pain (LBP) is the leading cause of disability worldwide, with prevalence doubling in the past 14 years. To date, prognostic screening tools display poor discrimination and offer no net benefit of screening over and above a 'treat all' approach. Characteristics of the primary sensory (S1) and motor (M1) cortices may predict the development of chronic LBP, yet the prognostic potential of these variables remains unknown. The Understanding persistent Pain Where it ResiDes (UPWaRD) study aims to determine whether sensorimotor cortex activity, an individual's capacity for plasticity and psychosocial factors in the acute stage of pain, predict LBP outcome at 6 months. This paper describes the methods and analysis plan for the development of the prediction model. Methods and analysis: The study uses a multicentre prospective longitudinal cohort design with 6-month follow-up. 120 participants, aged 18 years or older, experiencing an acute episode of LBP (less than 6 weeks duration) will be included. Primary outcomes are pain and disability. Ethics and dissemination: Ethical approval has been obtained from Western Sydney University Human Research Ethics Committee (H10465) and from Neuroscience Research Australia (SSA: 16/002). Dissemination will occur through presentations at national and international conferences and publications in international peer-reviewed journals. Trial registration number: ACTRN12619000002189; Pre-results.